10. Oblicz:
a) (-2 + 5) - (-3) =
e) (-13 – 8):(-3 + 10) =
b) (-3-8) · (8 - 12) =
f) (-3) · (2 – 7) – (-6 + 2) =
c) (5 - (-2)) · (3 – (-6)) =
g)
(13-18) – (17-(-3))
10-15
d)
4-(-6)
-2
4-(46)
h) -2 -(-3) -4.(-7)
=
7-9​


Odpowiedź :

Odpowiedź:

a) (-3) + 3 = 0

e) -21 : 7 = -3

b) -11 * (-4) = 44

f) (-3) * (-5) + 4 = 19

c) 7 * 9 = 63

g) niesprecyzowane działanie

d) niesprecyzowane działanie

h) - 2 -(-3) -4*(-7) = -2+3 + 28

7- 9 = -2

popraw te przykłady bo nie da sie zrozumieć jakie to działanie

Szczegółowe wyjaśnienie: